Incidence and Cause of Delirium in Hospitalized Patients between the Ages of 18 and 56: A Retrospective Chart Review. (28th January 2014) - Weckmann, Michelle T.; Bay, Camden; Abu Ata, Nesrin; Morrison, R. Sean
Abstract : Background . Delirium is a common and devastating condition which has been well characterized in elderly cancer patients, but little is known about delirium in cancer patients under the age of 65. Aim . A pilot study to explore the incidence and potential causes of delirium in hospitalized advanced cancer patients at the age of 18–56 years. Design . A retrospective chart review using validated instruments was used to examine the charts of hematology-oncology admissions in a large academic institution. Data was collected as to the likelihood of delirium and potential precipitants. Results . Delirium incidence was 29% among advanced cancer patients. The associated precipitants of delirium were multifactorial, the most common being medications and infection. Delirium was more common in patients admitted for either acute symptom management or the presence of a lung malignancy. Patients with delirium demonstrated significantly increased total hospital cost and a borderline significant result for increased mortality compared to those without delirium. Conclusions . Delirium is common in hospitalized advanced cancer patients (age 18–56 years) and the cause is typically multifactorial. Delirium results in a more complicated hospital course and likely increased mortality. Further research is needed to define strategies to prevent and treat this common and distressing condition.